Pemberdayaan Siswa Melalui Sosialisasi Dalam Pencegahan Bullying Di SDN 02 Sapan - Mutiara, Mutiara; Sari Mariati; Nur Hasanah; Muhammad Fauzan; Ade Putra; Musawir Al Ghani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Bullying at SDN 02 Sapan still often occurs, both in the form of fights and acts of teasing each otherbetween friends. Although teachers have given advice, bullying behavior continues to occur between students.Because, this activity aims to provide knowledge to students and schools about the forms and impacts of bullying, aswell as prevention efforts that can be taken by the school at SDN 02 Sapan. Bullying cases in elementary schoolsare serious problems that can have a negative impact on children's development, both psychologically and socially.Bullying not only interferes with the learning process, but can also reduce children's self-confidence and causelong-term trauma. This service aims to increase awareness and understanding of the dangers of bullying in the SDN02 Sapan environment through a socialization program involving students, teachers, and parents. The methods usedin this activity include providing interactive materials, group discussions, and creative activities as a form of antibullying commitment. Students are given an understanding of the definition of bullying, its forms, and the negativeimpacts it causes, while teachers and parents are given knowledge about how to recognize and handle bullyingcases. The main solution in dealing with bullying in elementary schools is collaboration between teachers andparents in motivating and developing student character.